Changes in the Biological Characteristics ofPlutella xylostellaUsing Ethanolic Plant Extracts - Couto, Irys Fernanda Santana; Souza, Silvana Aparecida; Valente, Fabricio Iglesias; Silva, Rosicleia Matias da; Paula Quintao Scalon, Silvana de; Pereira, Fabricio Fagundes; Silva, Sandra Verza da [UNESP]; Carvalho, Emerson Machado de; Mussury, Rosilda Mara (Springer, 2020)
The indiscriminate use of synthetic insecticides has led to the emergence of resistant populations ofPlutella xylostella L. (Lepidoptera: Plutellidae), hindering its control and causing economic damage to brassica production. Thus, in order to seek control alternatives, this study aimed at assessing the bioactivity of the ethanolic extracts ofSchinus terebinthifolius(Anacardiaceae),Annona coriacea(Annonaceae),Annona crassiflora(Annonaceae), andSerjania marginata(Sapindaceae) on the life cycle ofP. xylostella. Cabbage leaf discs were immersed in the treatments at a concentration of 10mg/mL and given daily to the larvae. Larval and pupal duration and survival, pupae weight, the longevity of males and females, number and survival of eggs, incubation period, and days of oviposition parameters were evaluated. All extracts differed significantly from the control in terms of larval and pupal duration, pupal survival, and pupae weight. All the extracts prolonged the larval and pupal period ofP. xylostella. OnlyA. coriaceadid not differ significantly from the control in terms of larval survival, and the highest larval mortality was observed in the treatment withS. marginata(50%). Pupal survival, pupae mass, oviposition period, and egg survival were reduced in all treatments with ethanolic extracts. The treatments withAnnonaandS. marginataspecies have reduced the number of eggs. Treatments withS. terebinthifoliusandS. marginatahave reduced the incubation time of eggs. Thus, the treatments with ethanolic plant extracts act on the life cycle ofP. xylostellanegatively impacting the biological parameters evaluated.
Keywords: Annona coriacea; Annona crassiflora; Plutella xylostella; INSECTICIDES plants; Serjania marginata; Schinus terebinthifolius